(untitled) (Al-Academy, 2024)
The research deals with a duet of an educational nature for two violins. The researcher composed it during the period from 2014 to 2016 as part of a series of similar pieces intended for students. In terms of level and performance, the piece was written so that the roles of both instruments are equal and complement each other strongly and in a contemporary style. The piece allows the first violin part to be played by the student and the second by the teacher, or it can be played by two students of the same level as well. The piece can also be played for the purpose of improving and learning violin playing techniques or presented in concerts as a local academic piece. The researcher tried to write a piece that is as contemporary as possible in all aspects such as form, harmony and counterpoint, in addition to evoking a good range of feelings and atmospheres in a concise musical framework and preserving the Iraqi Kurdish folk heritage as well. The research will benefit composers who wish to develop their local music and reformulate it academically. It is also useful for all students studying violin in Kurdish and Iraqi schools, such as institutes and colleges, especially those who are at the end of their academic years